2003
DOI: 10.1097/00002030-200311070-00001
|View full text |Cite
|
Sign up to set email alerts
|

Human epithelial β-defensins 2 and 3 inhibit HIV-1 replication

Abstract: This study shows for the first time that HIV-1 induces beta-defensin expression in human oral epithelial cells and that beta-defensins block HIV-1 replication via a direct interaction with virions and through modulation of the CXCR4 coreceptor. These properties may be exploited as strategies for mucosal protection against HIV-1 transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
458
6
10

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 400 publications
(489 citation statements)
references
References 41 publications
15
458
6
10
Order By: Relevance
“…Antimicrobial peptides such as defensins serve to combat bacterial and viral infection. Human beta-defensins (hBD) such as hBD-2 have been shown to exert anti-HIV activity (Quiñones-Mateu et al, 2003;Sun et al, 2005;Weinberg et al, 2006). hBD is upregulated in various cell types in response to bacterial infection and pro-inflammatory cytokines (Tsutsumi-Ishii et al, 2000;Wehkamp et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Antimicrobial peptides such as defensins serve to combat bacterial and viral infection. Human beta-defensins (hBD) such as hBD-2 have been shown to exert anti-HIV activity (Quiñones-Mateu et al, 2003;Sun et al, 2005;Weinberg et al, 2006). hBD is upregulated in various cell types in response to bacterial infection and pro-inflammatory cytokines (Tsutsumi-Ishii et al, 2000;Wehkamp et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that human oral epithelial cells expressed hBD-2 and 3 mRNA upon stimulation with HIV-1 virions (Quiñones-Mateu et al, 2003). We hypothesized that besides the HIV-1 virion, viral proteins such as HIV-1 Tat may contribute to up-regulate expression of hBD.…”
Section: Induction Of Hbd Expression By Hiv-1 Tat In Human B Cellsmentioning
confidence: 98%
See 3 more Smart Citations